Communicating cleanliness, health, safety, and environmental sustainability policy during Covid-19 - Isnaini, Santi; Setijaningrum, Erna; Angelia, Ruth Christien Pniel (Faculty of Communications Science, Dr. Soetomo University, 2022)
One of the key strategies for tourism and hospitality recovery post-Covid-19 is communicating the Cleanliness, Health, Safety, and Environmental Sustainability (CHSE) policy. CHSE policy ensures that tourism actors and tourists conduct a new tourism culture that coalesced with the global pandemic. Therefore, the current study offers a study case reviewing the communication of CHSE policy in Bromo Tengger Semeru (BTS) tourist areas. BTS is designated as one of the Indonesian government's national tourism strategic areas or New Bali with priority status. We reviewed published tourism and hospitality literature pandemic-related articles to meet our research objectives and conducted in-depth interviews with BTS community leaders. Based on the results, we identified that the communication of CHSE policy in the BTS area applies an ideation communication strategy, emphasising instructional, directional, and non-directional communication patterns. These communication patterns are implemented through the three categories of policy instruments that consider the people's cognitive, emotional, and social aspects of the BTS.